2022
DOI: 10.1128/mbio.02330-21
|View full text |Cite
|
Sign up to set email alerts
|

MGF360-9L Is a Major Virulence Factor Associated with the African Swine Fever Virus by Antagonizing the JAK/STAT Signaling Pathway

Abstract: African swine fever—an acute, febrile, hemorrhagic, highly contacting, and highly lethal disease caused by African swine fever virus (ASFV)—jeopardizes the global pig industry. Understanding the mechanism ASFV employs to evade host defense during infection is essential for developing targeted drugs and vaccines against ASFV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 47 publications
0
54
0
Order By: Relevance
“…The virulent 22653/14 strain seemed to have developed mechanisms to suppress the induction of several type I IFN genes (10).The highly virulent strain Lisboa60 could inhibit IFN production in macrophages using a way independent on IRF3 modulation (11). Additionally, multiple ASFV proteins were shown to contribute to the inhibition of type I IFN responses by targeting various innate immune pathways, such as the cGAS-STING pathway, Toll-like receptors pathway, JAK/STAT pathway and NF-kB pathway (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…The virulent 22653/14 strain seemed to have developed mechanisms to suppress the induction of several type I IFN genes (10).The highly virulent strain Lisboa60 could inhibit IFN production in macrophages using a way independent on IRF3 modulation (11). Additionally, multiple ASFV proteins were shown to contribute to the inhibition of type I IFN responses by targeting various innate immune pathways, such as the cGAS-STING pathway, Toll-like receptors pathway, JAK/STAT pathway and NF-kB pathway (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Another gene involved in disease production is MGF360-9L [ 42 ]. It was shown that the MGF360-9L gene is involved in the down-regulation of interferon expression.…”
Section: Identification Of Novel Determinants Of Virulence In the Asf...mentioning
confidence: 99%
“…For instance, TBK1 is inhibited (or degraded) by E120R ( Liu H. et al, 2021 ), DP96R ( Wang et al, 2018 ), MGF-360-11L ( Yang et al, 2022 ), and A137R ( Sun et al, 2022 ). Similarly, JAK/STAT are targeted by MGF-360-9L ( Zhang et al, 2022 ) and MGF-505-7R ( Li et al, 2021b ). Some ASFV proteins, like I226R ( Hong et al, 2022 ), I329L ( de Oliveira et al, 2011 ), and MGF-360-12L ( Zhuo et al, 2021 ) are able to target both the IFN and NF-κB pathways at the same time.…”
Section: Viral Antagonism Of Interferon and Nuclear Factor κB Pathway...mentioning
confidence: 99%